The Transition to Low-carbon Public Transport: An Equity Model of the Cost of Ownership of Electric Buses - Sirasoontorn, Puree; Wongcharoen, Petchtharin (Journal of Applied Economics and Management Strategy, 2023)
This paper aims to assess the effective adoption of electric buses by Bangkok Mass Transit Authority (BMTA) in the Bangkok Metropolitan Area to achieve low-carbon transition in public transport. In this study, the economic model of the total cost of ownership (TCO) is employed. TCO includes private costs and external costs from greenhouse gas emissions and air pollution. This paper also adopts the TCO parity model to analyze the long-term competitiveness of electric buses and assess the effectiveness of government measures to promote the use of electric buses. The results shows that diesel-powered buses are much more economically competitive than electric buses owing to the high purchase price of electric buses. Therefore, if the price of battery, which is a key component in electric buses, tends to fall, electric buses will reach TCO parity and be able to serve as a cost-effective replacement for diesel-powered buses by 2022. If the government aims to replace diesel-powered buses with electric buses immediately, this study found that the zero-interest loan program for electric buses would be the most effective government measure. In addition, if the useful lifespan of electric buses is extended, the electric buses will be more economical than other types of buses. Last but not least, the public transport will be transitioned toward low-carbon economy immediately if the government restructures diesel prices by eliminating the price subsidization through the Oil Fund.